2018 International Conference on Information and Communication Technology for the Muslim World (ICT4M) 2018
DOI: 10.1109/ict4m.2018.00028
|View full text |Cite
|
Sign up to set email alerts
|

A Business Case for Digital Transformation of a Malaysian-Based University

Abstract: The space of higher education has been receiving enough disruptions lately from the vast amount of advancements in technology. They are forced to adapt to the dynamic demands, tools, and other technological changes that can be overwhelming. This adaptation to technological changes is often referred as digital transformation, which is unavoidable, unless if the institution is ready to be deemed irrelevant. This paper will start the discussion on the topic of this transformation; the role of university, why the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Regarding the impact of digital transformation in the context of HEIs, recent research states that avoiding DT is not an option, and that HEIs are forced to adapt to technological changes if they want to stay relevant [30]. In the same vein, it is argued that implementing new technologies is inevitable, that HEIs must obligatorily implement new technologies to be digitally relevant, and that the real challenge is the right execution of available digital plans and strategies, engaging and empowering students, staff, and the faculty in the process [31].…”
Section: Digital Transformation Business Model Innovation and Heimentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the impact of digital transformation in the context of HEIs, recent research states that avoiding DT is not an option, and that HEIs are forced to adapt to technological changes if they want to stay relevant [30]. In the same vein, it is argued that implementing new technologies is inevitable, that HEIs must obligatorily implement new technologies to be digitally relevant, and that the real challenge is the right execution of available digital plans and strategies, engaging and empowering students, staff, and the faculty in the process [31].…”
Section: Digital Transformation Business Model Innovation and Heimentioning
confidence: 99%
“…DT is considered as both positive and necessary, and an opportunity to professionalize the HEI, and to better satisfy students' needs and digital expectations. The HEI is feeling the pressure to constantly adopt new technologies and processes to remain a relevant player, as prior research has shown [30,31]. As an example, HEIs feel the need to do more with experimenting with massive open online courses (MOOCs), to follow education trends [9].…”
Section: Contributions Of the Papermentioning
confidence: 99%
“…The dimensions of the digital transformation processes are teaching (digital platforms and content for teaching and learning, innovative pedagogical methodologies, digital literacy and digital skills and the teaching management process) [22][23][24], infrastructure (digital media for teaching, security and data, and software for universities) [25,26], curriculum (its modernization and digital curriculum) [27,28]; administration (technological financing, reorganization of administrative units and informed decision-making) [29,30]; research [31]; human resources [32,33]; extension [34,35]; governance of the digital transformation [22,25,34]; information and marketing [36,37] and business processes [26,29,34,36].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, digital transformation is an organization shift on all levels (Grajek, 2020; Orellana et al, 2019), a creation of a new business model (Powell et al, 2015), a redefinition of the whole business model (Berman, 2012;CISCO, n.d.), a new business model driven by the changes (Minina & Mabrouk, 2019;Wildan Zulfikar et al, 2018). The result of the digital transformation is to enable new processes (Grajek, 2020;Orellana et al, 2019;Powell et al, 2015), to offer a product or service with new features (Limani et al, 2019), through smart integration of digital technologies, processes and competences (I-SCOOP, n.d.-b) and a cultural, organizational, and operational change of an organization (Grajek, 2020;I-SCOOP, n.d.-b;Orellana et al, 2019).…”
Section: Increasing the Digital Maturity Of A Heimentioning
confidence: 99%
“…Higher Education Institutions are involved in an evolution to a new model of university. Cawood (2018) and Wildan Zulfikar et al (2018) describe some of the drivers of change that will shape the university of the future: increasing competition, digital behavior, changes in work, global mobility, democratization of knowledge and access, continuous learning, and removal of boundaries within industries. Similarly, Bloomberg (2018) and I-SCOOP (n.d.-b) include cultural change, customer-centric changes, and overall business-ecosystem changes.…”
Section: Introductionmentioning
confidence: 99%